2022
DOI: 10.1002/smll.202204070
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Engineering and Recrystallization of Perovskite Quantum‐Dot Thin Film for Low‐Threshold Plasmonic Lattice Laser

Abstract: Solution‐process perovskite quantum dots (QDs) are promising materials to be utilized in photovoltaics and photonics with their superior optical properties. Advancements in top‐down nanofabrication for perovskite are thus important for practical photonic and plasmonic devices. However, different from the chemically synthesized nano/micro‐structures that show high quality and low surface roughness, the perovskite QD thin film prepared by spin‐coating or the drop‐casting process shows a large roughness and inhom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The details of the model calculation are explained in the SI (section 2.6). Furthermore, recent studies of plasmonic and photonic structures ,, and their mutual couplings with CsPbBr 3 NCs stress the importance of our findings, whereby LHP NC assemblies are manipulatable to induce novel interactions with the external medium, for exploring future technology and applications.…”
Section: Resultsmentioning
confidence: 72%
“…The details of the model calculation are explained in the SI (section 2.6). Furthermore, recent studies of plasmonic and photonic structures ,, and their mutual couplings with CsPbBr 3 NCs stress the importance of our findings, whereby LHP NC assemblies are manipulatable to induce novel interactions with the external medium, for exploring future technology and applications.…”
Section: Resultsmentioning
confidence: 72%
“…The RMS roughness of films 1, 2, 3, 4, and 5 are 2.9 1.9, 2.3, 3.4, and 4.1 nm, respectively, as summarized in Figure f. All the above characterization suggests that the morphology and microscopic structures of P2F8 film can be optimized through the engineered spin coating process, which is of significant importance for the realization of CW lasers and plasmonic lasers. , …”
Section: Resultsmentioning
confidence: 89%
“…All the above characterization suggests that the morphology and microscopic structures of P2F8 film can be optimized through the engineered spin coating process, which is of significant importance for the realization of CW lasers and plasmonic lasers. 44,45 PL spectroscopy and laser gain properties of these quasi-2D perovskite thin films are investigated using a 343 nm microscopic femtosecond laser. As shown in Figure 5a, the PL spectrum of film 2 at low pump densities (<11 μJ/cm 2 ) shows a central wavelength of 547 nm and a fwhm width of 26.75 nm corresponding to a spontaneous emission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[57,58] Laser irradiation on a solution or film of perovskite precursors can trigger chemical reactions and generate PQDs. [59][60][61] Gao et al reported the in situ fabrication and patterning of crystallized CsPbBr 3 /CsPb 2 Br 5polymer nanocomposites using a 532 nm fs laser (Figure 3a). [62] With laser irradiation, nonlinear absorption resulted in the polymerization of the g-butyrolactone solvent with saturated perovskite precursors, which contributed to the localized growth of PNCs.…”
Section: Lip Quantum Dots and Nanocrystalsmentioning
confidence: 99%